2021
DOI: 10.1111/hdi.12939
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylpyrrolidone in hemodialysis membranes: Impact on platelet loss during hemodialysis

Abstract: Introduction: Hydrophilic modification with polyvinylpyrrolidone (PVP) increases the biocompatibility profile of synthetic dialysis membranes. However, PVP may be eluted into the patient's blood, which has been discussed as a possible cause for adverse reactions rarely occurring with synthetic membranes. We investigated the content of PVP and its elution from the blood-side surface from commercially available dialyzers, including the novel FX CorAL, with PVP-enriched and α-tocopherol-stabilized membrane, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 38 publications
3
34
1
Order By: Relevance
“…The reduced albumin adsorption seen over the first hour with FX CorAL 600 is thought to originate from the dialyzer membrane's almost neutral surface charge and its higher PVP concentration on the inner surface, which stabilizes a membrane-protective hydro layer [ 12 ]. It is important regarding tolerability that this high PVP concentration on the FX CorAL's membrane does not lead to high elution [ 27 ]. Recent in vitro experiments indicated that PVP elution is different between dialyzers and depends on membrane material and method of sterilization [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced albumin adsorption seen over the first hour with FX CorAL 600 is thought to originate from the dialyzer membrane's almost neutral surface charge and its higher PVP concentration on the inner surface, which stabilizes a membrane-protective hydro layer [ 12 ]. It is important regarding tolerability that this high PVP concentration on the FX CorAL's membrane does not lead to high elution [ 27 ]. Recent in vitro experiments indicated that PVP elution is different between dialyzers and depends on membrane material and method of sterilization [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important regarding tolerability that this high PVP concentration on the FX CorAL's membrane does not lead to high elution [ 27 ]. Recent in vitro experiments indicated that PVP elution is different between dialyzers and depends on membrane material and method of sterilization [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fall in platelet count observed with polysulfone membranes has been attributed to platelet activation, rather than complement activation, as revealed in the recent decades, during cuprophane membrane use [36]. Conversely, synthetic membranes based on polysulfone or polyethersulfone, but blended with polyvinylpyrrolidone as a hydrophilic agent, had an excellent biocompatibility profile, reducing protein fouling and platelet adsorption [37,38]. Furthermore, the use of heparin does not block the coagulation and platelet activation steps, unlike the more effective anticoagulant citrate.…”
Section: Platelets and Coagulation Systemmentioning
confidence: 99%
“…Pro-thrombotic status mediated by activated intrinsic and extrinsic pathways leading to pro-inflammatory effects and endothelial cell damage Platelet dysfunction with atypical activation D-dimer, β-TG TAT Anticoagulant citrate [39,40] Polyvinylpyrrolidone [37,38] Oxidative Stress…”
Section: Coagulation System and Platelet Activitymentioning
confidence: 99%
“…Recent in vitro studies found substantial differences in the PVP content and elution as well as in the secondary membrane formation of different dialyzer membranes 17,21 . These studies investigated the novel FX CorAL dialyzer, which was developed to achieve positive effects on hemocompatibility via increased and stabilized PVP on the blood‐side surface of the membrane.…”
Section: Introductionmentioning
confidence: 99%